Preparing for DB2 near-realtime business intelligence - Ballard, Chuck (IBM redbooks., 2004)
In this IBM Redbooks publication we discuss primary processes and various alternatives that prepare you in implementing a DB2 near-realtime business intelligence environment. We discuss architectural alternatives and include overviews of software products that you can use in an implementation. As a primary focus, we tested the capabilities for supporting continuous update of a DB2 data warehouse while running a continuous concurrent query workload against that data warehouse. We tested several implementation scenarios and the variables that impact them. The results of our testing and the issues we encountered are provided. We used an IBM p-Series multiprocessor, along with a number of software products, including WebSphere MQ, DB2 MQ Listener, DB2 UDB, and DB2 Information Integrator - Replication Edition. We discuss ETL processing in a near-realtime environment, with reference to DB2 Warehouse Manager and DataStage from Ascential Software. We used WebSphere Studio Application Developer to generate online query applications, along with Java, SQL, and C-based stored procedures. We discuss DB2 Query Patroller and DB2 Governor. We provide guidelines and recommended best practices, and this book is what you need to get prepared to implement near-realtime business intelligence in your environment.